Sanksi Hukum Pidana Islam Terhadap Negara - Taufik Ismail Ramadhan; Deden Najmudin (Melati Institute, 2023)
This article aims to examine the sanctions of Islamic criminal law for the state, namely the punishment given to the state that violates Islamic criminal law. This article uses normative juridical research method by examining the sources of Islamic criminal law, such as the Qur'an, Hadith, Ijma, and Qiyas, as well as comparison with national and international criminal law. This article finds that Islamic criminal law sanctions for the state are divided into three categories, namely Hudud, Qisas, and Ta'zir. Hudud is a punishment that is fixed and cannot be changed, such as the death penalty, the punishment of cutting hands, flogging, stoning, and exile. Qisas is a punishment that is reciprocal and can be modified, such as the death penalty, the punishment of wounds, the punishment of fines, and the punishment of daman. Ta'zira is a flexible and customizable punishment, such as imprisonment, fines, flogging, dismissal, inclusion in the list of despicable persons, and others. Islamic criminal law sanctions for the state have important functions, namely preventive function, repressive function, educative function, rehabilitative function, and reformative function. This article also discusses the requirements, process, and implementation of Islamic criminal law sanctions for the state, as well as challenges and solutions.